Access to affordable daycare and women's economic opportunities: evidence from a cluster-randomised intervention in India. Issue 3 (2nd July 2020) - Nandi, Arijit; Agarwal, Parul; Chandrashekar, Anoushaka; Harper, Sam
ABSTRACT: We used data from a cluster-randomized trial in rural Rajasthan, India to evaluate the impact of providing access to a community-based daycare program on women's economic outcomes two years later. The sample included 2858 mothers with age-eligible children. Providing access to daycare led 43% of households to utilize them. The intervention reduced time on childcare by 16.0 minutes/day (95%CI=-10.6, 42.5) and increased the probabilities that women were paid in cash and spent time during the prior day on paid work by 2.3 (95%CI=0.0, 4.5) and 2.6 (95%CI=0.9, 4.4) percentage points. Other indicators of labor force participation and income were unaffected.